Gut microbiota-dependent adaptor molecule recruits DNA methyltransferase to the TLR4 gene in colonic epithelial cells to suppress inflammatory reactions - Narabayashi, Hikari; Koma, Chiharu; Nakata, Kazuaki; Ikegami, Mion; Nakanishi, Yusuke; Ogihara, Jun; Tsuda, Masato; Hosono, Akira; Hanazawa, Shigemasa; Takahashi, Kyoko (Frontiers in Molecular Biosciences, 2022)
The intestine is inhabited by a large number of commensal bacteria that are immunologically non-self, potentially causing inflammation. However, in a healthy intestine, inflammation is strictly controlled at low levels to maintain homeostasis. We previously reported that the gut microbiota induce DNA methylation of the gene encoding TLR4, a pattern recognition receptor that recognizes lipopolysaccharides of gram-negative bacteria, in colonic epithelial cells, suggesting its role in controlling intestinal inflammation. However, there remains a question of how gut microbiota cause methylation of only specific genes including TLR4, despite the fact that DNA methyltransferase (DNMT) is common to all genes targeted for methylation. Here, we identified RBM14 as an adaptor molecule that recruits DNMT to the TLR4 gene. RBM14 was shown to bind DNMT3 and be expressed at significantly higher levels in an intestinal epithelial cell (IEC) line with hypermethylated TLR4 gene than in an IEC line with hypomethylated TLR4 gene. In addition, RBM14 interacted with DNA regions of the TLR4 gene, and knockdown of RBM14 suppressed DNA methylation of the TLR4 gene in IECs. Furthermore, RBM14 expression was higher in colonic epithelial cells of conventional mice than in those of germ-free mice. Collectively, these results indicate that the gut microbiota induce methylation of the TLR4 gene in colonic epithelial cells by upregulating RBM14, which can recruit DNMT3 to the gene. The regulation of adaptor molecules such as RBM14, which bind to specific target genes and recruit DNMT, can explain, at least in part, how gut microbiota contribute to the maintenance of intestinal homeostasis through epigenetic control of specific gene expression in IECs.